Climate change mitigation and adaptation strategies in drylands of Northern Karnataka - DUPDAL, RAVI; PATIL, B L; MANJUNATHA, B L; PATIL, S L (The Indian Journal of Agricultural Sciences, 2022)
This study was carried out in Vijayapura and Bagalkot districts of Karnataka to assess the adoption of improved technologies by dryland farmers to mitigate effects of climate change. Primary data was collected from 240 farmers using multi-stage random sampling technique. Nearly 70% farmers experienced the decreased and uneven distribution of rainfall, 35% farmers experienced untimely rainfall and 48% farmers experienced increase in temperature. This unpredictable variation in climate especially rainfall and temperature resulted in decreased crop yields, frequent crop failures, sinking water level in bore wells and open wells and increased emergence of pest and diseases. The farmers in the region sustained crop yields by adopting climate resilience indigenous and modern scientific technologies like manipulating sowing dates, mixed farming, crop diversification, alternate cropping systems and drought tolerant varieties.The age of farmer, access to irrigation, level of education, farming experience, social participation, land holding size, livestock possession and institutional credit had significant impact on adoption of climate resilient technologies by the farmers in the region.